Kurdish Students’ Motivation to Study in Hungary - Sana Khudur (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The present study intends to explore the motivation of Kurdish students to study in Hungary. To answer the query of the study; an in-depth qualitative interview method was employed. Nine higher education level students (BA, MA or PhD), five males and four females who are studying at four different universities in Hungary were interviewed. Individual face to face interviews were organised to engage into the details of what could be achieved from the participants and to discover their study experiences deeply. Based on the collected data outcomes; a process model of Kurdish student motivation to study in Hungary was designed which identifies the main stages of their motivational behavior in a process way from the initial wishes to accomplishments. The findings reveal that several reasons have impacts on responders` decision making and the choice of country. Also, the participants are highly motivated on their studies because of the future accomplishments they could gain as the result of pursuing their studies abroad and getting an international qualification.